Response of tilapia (Oreochromisniloticus) behaviour to salinity differences: a laboratory scale study. Issue 1 (February 2021) - Fuadi, A A; Hasly, I R J; Azkia, L I; Irham, M
Abstract: Tilapia is one of the important commodities of freshwater aquaculture in Indonesia which has good immunity and adaptability. One of the adaptations that can be made by Tilapia is physiological adaptation to a high salinity range. Information on the resistance of Red Tilapia to different salinity on a laboratory scale provides basic information to test the use of Red Tilapia bait as an alternative bait in the Tuna longline fishery. The purpose of this study was to determine the behaviour and mortality rate of Red Tilapia ( Oreochromis niloticus) to differences in salinity. This research was conducted at the Laboratory of fish behavior, Bogor Agricultural University in May 2018 with three stages. The first stage is the acclimatization of the test fish in the maintenance aquarium which is carried out in one week. The second stage is to calculate the salinity in water by diluting the desired salinity. The third stage tested the differences in salinity levels on the behavior of the fish in the experimental aquarium. Comparative descriptive statistical analysis was used by comparing Tilapia between various salinity treatments. The random design used in this study was a randomized block design, namely between salinity and the length of time the fish remained in the aquarium. The behaviour of Tilapia during changes in salinity was light stress at salinity 10 and 20 ppt. However, when it rises to 30 ppt the fish are already experiencing severe stress, which is indicated by erratic swimming directions and the number of opercula that are getting slower.